2015
DOI: 10.1136/bmjopen-2014-007533
|View full text |Cite
|
Sign up to set email alerts
|

A study of urgent and emergency referrals from NHS Direct within England

Abstract: ObjectivesThe presented study aimed to explore referral patterns of National Health Service (NHS) Direct to determine how patients engage with telephone-based healthcare and how telephone-based healthcare can manage urgent and emergency care.SettingNHS Direct, England, UKParticipantsNHS Direct anonymised call data (N=1 415 472) were extracted over a representative 1-year period, during the combined month periods of July 2010, October 2010, January 2011 and April 2011. Urgent and emergency calls (N=269 558; 19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…11,12 Furthermore, GPs more often triaged older patients to faceto-face contacts, which could be related to higher frequency of comorbidity and higher likelihood of a severe acute health problem. [13][14][15] Moreover, a problem persisting for 12-24 hours could indicate a (sub) acute problem that needs relatively quick treatment, indicating a need for consultation in particular during weekends when own GP is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Furthermore, GPs more often triaged older patients to faceto-face contacts, which could be related to higher frequency of comorbidity and higher likelihood of a severe acute health problem. [13][14][15] Moreover, a problem persisting for 12-24 hours could indicate a (sub) acute problem that needs relatively quick treatment, indicating a need for consultation in particular during weekends when own GP is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…The Public Health England (PHE) Real-time Syndromic Surveillance Team established a telehealth syndromic surveillance system in 2001 to monitor calls to the National Health Service (NHS) Direct telephone helpline (NHS Direct) [9]. During 2013 NHS Direct was replaced in England by a new service, NHS 111 [10]; PHE subsequently developed a new national syndromic surveillance telehealth system based upon the daily calls received by NHS 111 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Routine data from 21 Dutch cooperatives showed higher OOHS use in neighbourhoods with more non-Western immigrants33 while national data from Norway showed that migrant groups had lower emergency primary care contact rates overall although rates were higher for specific migrant groups 39. In England, TTA data found that, following contact with NHS Direct, white British or Bangladeshi children were most likely to be referred to urgent care services including OOHS while children of Indian and ‘other white’ ethnicity were least likely to be referred 40…”
Section: Resultsmentioning
confidence: 99%